Immune‐related adverse events in the gastrointestinal tract: diagnostic utility of upper gastrointestinal biopsies. Issue 2 (13th November 2019) - Zhang, M. Lisa; Neyaz, Azfar; Patil, Deepa; Chen, Jonathan; Dougan, Michael; Deshpande, Vikram
Abstract : Aims: Immune checkpoint inhibitors (ICIs) improve survival across a range of malignancies but are also associated with a spectrum of gastrointestinal (GI) immune‐related adverse events (GI‐irAEs). The aims of this study were to explore the diagnostic value of gastric and duodenal biopsies and to address considerations in the differential diagnosis. Methods and results: We identified 39 patients who were treated with ICIs and had a subsequent upper GI biopsy. We recorded clinical data and endoscopic findings, and reviewed their gastric, duodenal and colonic biopsies. Twenty‐one (54%) patients were treated with an anti‐programmed cell death protein 1 (PD‐1)/anti‐programmed cell death ligand 1 antibody alone, and 17 (44%) patients were treated with a combination of anti‐cytotoxic T‐lymphocyte‐associated protein‐4 and anti‐PD‐1 antibodies. Thirty‐two (82%) patients presented with diarrhoea. Gastric alterations included periglandular inflammation and granulomas, and duodenal changes included villous blunting, intraepithelial lymphocytosis, granulomas, and neutrophilic activity. We recognised four patterns of colonic injury: (i) acute self‐limiting colitis; (ii) lymphocytic colitis; (iii) collagenous colitis; and (iv) apoptosis‐only. Twenty‐nine (74%) and 10 (26%) patients were diagnosed clinically as positive and negative for GI‐irAEs, respectively. Gastric periglandular inflammation ( P  = 0.004) and an increased number of colonic lamina propria mononuclear cells ( P  = 0.04) correlated with the clinical diagnosis of a GI‐irAE. Histological alterations associated with ICI injury were more often identified in upper GI biopsies (71%) than in colonic biopsies (65%). Conclusions: The morphological spectrum of ICI‐related GI disease is broad, and mimics a range of infectious and inflammatory diseases. Gastric periglandular inflammation represents one of the more characteristic histological features of GI‐irAEs. The study underscores the importance of a comprehensive review of upper and lower GI biopsies for the diagnosis of GI‐irAEs.